Change of differential diagnosis tactics in the process of clinical observation ofa patient - O. V. Kalinina (Бюллетень сибирской медицины)
The complicated ratios of clinical symptoms of internal lesions during central lung cancer are demonstrated in the article when changes of differential diagnosis tactics were required for diagnosing that necessary keeping is priority of the clinical appraisal of the results inspection patient.